Newspaper Coverage of PVC Registration and Collection Against 2023 Presidential Election in Nigeria - Ozioko, Obioma R.; Apeh, Andrew C.; Udeze, Sunny E.; Etumnu, Emeka Williams (Academic Journal of Da'wa and Communication, 2024)
It appears that within the time frame of this study there was a low newspaper coverage on PVC registration and collection. Even for an important issue as PVC Registration and Collection in Nigeria. In some other cases, the placements of PVC registration and collection stories are placed at the least noticeable space in the select newspapers used. This problem necessitated the study hence; the researchers assessed Guardian and Daily Sun newspapers coverage of PVC registration and collection. The researchers hinged this study on Agenda setting theory. This study employed the descriptive content analysis research design. The population used for the study was 730 newspaper editions. A sample size of 168 was arrived at whereas the composite month sampling technique was employed for the study. The code sheet and guide were the instruments for data collection. Finding from the study showed that PVC registration and collection was given low frequency of coverage, it was as well placed more in inside pages of newspapers, as for the depth, they were given more of 1/4 page depth and were reported in a neutral direction. It was concluded that Guardian and Daily Sun give less space, depth and frequency when reporting permanent voter’s card registration and collection much depth, to help their voter card registration and collection.